Determination of the Equivalent Ratio of Optimum Gasifier with Several Types of Biomass - Sumirat, Tito; Pradana, M. Rizky; Surjosatyo, Adi (Journal of World Science, 2023)
This study aims to create a CFD model aligned with lab test results from previous studies, conduct simulation tests using several types of biomass as input and optimize the operating parameters of various types of biomass to produce optimum syngas. The method used in this research is literature study and modelling using Ansys Fluent software. The results of this study indicate that biomass is a source of new and renewable energy (EBT) which has abundant potential in Indonesia, but its use could be more optimal. Biomass gasification is one of the most promising techniques used to convert solid fuels into useful gaseous fuels, which can be widely used in many households and industrial applications such as power generation and internal combustion engines. This research implies that it can help determine the optimum equivalence ratio and feed rate for a gasifier that utilizes various types of biomass. By finding the optimal combination, the composting process can achieve higher energy efficiency, resulting in more energy being generated from the biomass used. Additionally, by knowing the appropriate equivalence ratio and feed rate, this research can assist in optimizing the biomass composting process in the gasifier.